2021
DOI: 10.1158/2159-8290.cd-20-0839
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Subtypes of B-cell Lymphoma Revealed by Microenvironmental Signatures

Abstract: Diffuse large B-cell lymphoma (DLBCL) is a biologically and clinically heterogenous disease. Transcriptomic and genetic characterization of DLBCL have increased the understanding of its intrinsic pathogenesis and provided potential therapeutic targets. However, the role of the microenvironment in DLBCL biology remains less understood. Here, we performed a transcriptomic analysis of the microenvironment of 4,655 DLBCLs from multiple independent cohorts and described four major lymphoma microenvironment categori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
215
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(230 citation statements)
references
References 86 publications
14
215
0
1
Order By: Relevance
“…B cell lymphomas are among the most frequent hematopoietic malignancies and represent a molecularly heterogeneous group of diseases with different therapeutic vulnerabilities (26,117) and clinical outcomes that largely depend on a complex interplay between a multitude of genomic alterations and heterogeneous tumor microenvironment signatures (118,119). Sequencing studies allowed the identification of recurrently mutated genes that drive lymphomagenesis and led to refine DLBCL classification that pave the way for personalized therapeutic strategies (14,19,118).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B cell lymphomas are among the most frequent hematopoietic malignancies and represent a molecularly heterogeneous group of diseases with different therapeutic vulnerabilities (26,117) and clinical outcomes that largely depend on a complex interplay between a multitude of genomic alterations and heterogeneous tumor microenvironment signatures (118,119). Sequencing studies allowed the identification of recurrently mutated genes that drive lymphomagenesis and led to refine DLBCL classification that pave the way for personalized therapeutic strategies (14,19,118).…”
Section: Discussionmentioning
confidence: 99%
“…The latest large-scale genome sequencing studies identified up to seven different molecular subtypes of DLBCL (118) which represent an interesting framework for the development of models mimicking each molecular subtype. Now, recent DLBCL classifications based of TME composition revealed four distinct microenvironment compositions which provide independent contributions to clinical outcome regardless of the GCB/ABC cell-of-origin or the genetic DLBCL subtype classification (119). The challenge of modeling future preclinical mouse models will be to recapitulate both the genomic features of the tumors and the parallel remodeling of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large cohort study of lymphoma is showing the importance of a tumor microenvironment and its clinical importance. They identified novel microenvironments subtypes by defining 25 functional gene expression signatures reflecting pathway activities from transcriptome data [38]. Genomic data was analyzed to identify cancer clones by their unique mutational signatures [39].…”
Section: Tumor Heterogeneity: Cancer Genomics To Translational Medicinementioning
confidence: 99%
“…Schematic representation of the predominant cells in the microenvironment of the four DLBCL subgroups with prognostic significance, described by Kotlov et al . 70 (GC-like, germinal center-like; MS, mesenchymal; IN, inflammatory; and DP, depleted).…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%